EXAMINATION of PROSPECTIVE TURKISH LANGUAGE TEACHERS and TURKISH LANGUAGE and LITERATURE TEACHERS’ SELF-EFFICACY BELIEFS - Ayla ARSEVEN; Burcu MOROĞLU; Ebru ALDIĞ (International Journal of Eurasia Social Sciences, 2015)
The aim of this study is to examine self-efficacy beliefs of prospective Turkish Language and Turkish Language and Literature teachers and to find out the role of self-efficacy perception in education. This study is a phenomenological study, which is one of the qualitative research designs. Interviews were made as data collection tool. The study was carried out with a total of 30 students, 14 of whom are male and 16 of whom are female students, attending Cumhuriyet University Education Faculty and Faculty of Letters. 15 students from each faculty were included in the study. In data analysis process, content analysis method has been used. According to the findings of the study, “improvement of thinking skills”, “motivating for the course”, “using consolidator reinforce”, “content knowledge”, “improve four basic language skills” and “giving positive feedback and correction” themes emerged. As a result of the study, it was found out that prospective Turkish language teacher candidates attached greater importance to pedagogy, for Turkish Language and Literature teacher candidates “content knowledge” is the most important factor in teacher self-efficacy. Both prospective teachers groups stated that they will use student centered methods and techniques like brain storming, group work; however, they did not give any examples of these techniques and methods aimed to improve creative thinking and problem solving skills.debates on abortion research paper on abortion nyc abortion clinics